2016
DOI: 10.4082/kjfm.2016.37.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coffee Consumption on the Progression of Type 2 Diabetes Mellitus among Prediabetic Individuals

Abstract: BackgroundA previous large-scale cohort study investigated the relationship between coffee intake and the progression of diabetes mellitus in the United States. However, studies on the effects of coffee on diabetes are rare in South Korea. Therefore, this study assessed the amount and method of coffee intake in Koreans in order to determine if coffee intake has a prophylactic effect on diabetes progression.MethodsThis study included 3,497 prediabetic patients from a single medical institution, with glycated he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…( 11 ) , which found an inverse association between coffee intake and the risk of incident prediabetes and T2DM in individuals with known T2DM-related genetic mutations. Further studies have reported that coffee may lower the risk of developing T2DM or reduce the likelihood of progression from prediabetes to diabetes ( 23 , 26 , 39 , 40 ) . However, no previous study to our knowledge has identified an association between coffee consumption and prediabetes in a population-based sample.…”
Section: Discussionmentioning
confidence: 99%
“…( 11 ) , which found an inverse association between coffee intake and the risk of incident prediabetes and T2DM in individuals with known T2DM-related genetic mutations. Further studies have reported that coffee may lower the risk of developing T2DM or reduce the likelihood of progression from prediabetes to diabetes ( 23 , 26 , 39 , 40 ) . However, no previous study to our knowledge has identified an association between coffee consumption and prediabetes in a population-based sample.…”
Section: Discussionmentioning
confidence: 99%
“…The previous report also showed that consumption of coffee, particularly instant coffee mix, may result in weight gain and insulin resistance and may have harmful effects on metabolic syndrome, perhaps partly deriving from excessive intake of sugar and powder creamer[ 4 , 42 ]. The Kaplan-Meier survival analysis revealed that the risk of diabetes progression was lowest in patients who drank black coffee three or more times per day[ 43 ]. The instant coffee mix that contains nondairy creamer and/or sugar may have offset the potential benefit of coffee[ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic elevated blood glucose below the range of T2DM diagnosis represents a risk factor for cardiovascular disease and mortality (9). The proportion of progression of what is defined as "prediabetes" to T2DM remains unclear, however it has been described that up to 70% of prediabetes cases will eventually progress to T2DM, at a rate of 5% to 10% per year (10)(11)(12). Additionally, potential confounders such as body mass index, abdominal obesity, family history of T2DM, hypertension, cholesterol level, and low physical activity may potentially interfere with the progression from prediabetes to T2DM (11).…”
Section: Introductionmentioning
confidence: 99%